2017
DOI: 10.1177/0363546517740845
|View full text |Cite
|
Sign up to set email alerts
|

Men and Women Differ in the Biochemical Composition of Platelet-Rich Plasma

Abstract: Variability in the proteomic profile of PRP may affect tissue and clinical responses to treatment. These data suggest that clinical studies should account for the composition of PRP used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
88
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(95 citation statements)
references
References 80 publications
3
88
3
1
Order By: Relevance
“…Batch‐to‐batch consistency in HPL batches seems to require the pooling of 40 to 50 PC donations, corresponding to approximately 250 donors when using “random‐donor” PCs. Pooling minimizes inherent donor‐to‐donor variability due to impact of age or sex, such as the content in growth factors and other cell growth–promoting molecules, which are important components for growth medium supplementation . However, pooling increases the risk of contamination by 1) window period donations, 2) viruses that are not tested for, or 3) emerging agents, making the implementation of virus/pathogen inactivation procedures required .…”
Section: Discussionmentioning
confidence: 99%
“…Batch‐to‐batch consistency in HPL batches seems to require the pooling of 40 to 50 PC donations, corresponding to approximately 250 donors when using “random‐donor” PCs. Pooling minimizes inherent donor‐to‐donor variability due to impact of age or sex, such as the content in growth factors and other cell growth–promoting molecules, which are important components for growth medium supplementation . However, pooling increases the risk of contamination by 1) window period donations, 2) viruses that are not tested for, or 3) emerging agents, making the implementation of virus/pathogen inactivation procedures required .…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, another study of plateletrich plasma found that PDGF-BB was higher in men and found no sex differences in IGF-1 levels [374]. The same study also found that interleukin-1 beta (IL-1β) and several angiogenic growth factors, including tumor necrosis factor-alpha (TNF-α), basic fibroblast growth factor (bFGF), and transforming growth factor-beta 1(TGF-β1) were higher in males [374]. Further studies do not show a strict pro-angiogenic correlation in females versus males in serum; anti-angiogenic factor angiopoietin-2 and pro-angiogenic factor IL-3 were higher in females, while anti-angiogenic thrombospondin (TSP) and several pro-angiogenic endothelial adhesion molecules (E-selectin, VCAM-1) were higher in males [375].…”
Section: Sex Differences In Angiogenesismentioning
confidence: 94%
“…Finally, females and males have different amounts of circulating pro-angiogenic and anti-angiogenic factors, which may further contribute to the sex differences in tumor angiogenesis epidermal growth factor (EGF), insulin growth factor-1 (IGF-1), PDGF-BB, and VEGF, were significantly higher in women [373]. Conversely, another study of plateletrich plasma found that PDGF-BB was higher in men and found no sex differences in IGF-1 levels [374]. The same study also found that interleukin-1 beta (IL-1β) and several angiogenic growth factors, including tumor necrosis factor-alpha (TNF-α), basic fibroblast growth factor (bFGF), and transforming growth factor-beta 1(TGF-β1) were higher in males [374].…”
Section: Sex Differences In Angiogenesismentioning
confidence: 99%
“…PRP contains a mixture of growth factors (GFs), cytokines, and other proteins. Recent studies show high variability in the levels of GFs and inflammatory mediators (IMs) between males and females, between different individuals, and between samples from the same individual depending on timing and method of preparation . The multiple sources of variability in PRP composition substantially complicate understanding mechanisms of action and evaluation of clinical effectiveness …”
mentioning
confidence: 99%